Isolation of myocardial L-type calcium channel gating currents with the spider toxin omega-Aga-IIIA (The Rockefeller University Press, 1994)
The peptide omega-agatoxin-IIIA (omega-Aga-IIIA) blocks ionic current through L-type Ca channels in guinea pig atrial cells without affecting the associated gating currents. omega-Aga-IIIA permits the study of L- type Ca channel ionic and gating currents under nearly identical ionic conditions. Under conditions that isolate L-type Ca channel currents, omega-Aga-IIIA blocks all ionic current during a test pulse and after repolarization. This block reveals intramembrane charge movements of equal magnitude and opposite sign at the beginning of the pulse (Q(on)) and after repolarization (Q(off)). Q(on) and Q(off) are suppressed by 1 microM felodipine, saturate with increasing test potential, and are insensitive to Cd. The decay of the transient current associated with Q(on) is composed of fast and slow exponential components. The slow component has a time constant similar to that for activation of L-type Ca channel ionic current, over a broad voltage range. The current associated with Q(off) decays monoexponentially and more slowly than ionic current. Similar charge movements are found in guinea pig tracheal myocytes, which lack Na channels and T-type Ca channels. The kinetic and pharmacological properties of Q(on) and Q(off) indicate that they reflect gating currents associated with L-type Ca channels. omega-Aga-IIIA has no effect on gating currents when ionic current is eliminated by stepping to the reversal potential for Ca or by Cd block. Gating currents constitute a significant component of total current when physiological concentrations of Ca are present and they obscure the activation and deactivation of L-type Ca channels. By using omega- Aga-IIIA, we resolve the entire time course of L-type Ca channel ionic and gating currents. We also show that L- and T-type Ca channel ionic currents can be accurately quantified by tail current analysis once gating currents are taken into account.